Structural and functional characterization of gut microbiota in dyslipidemic patients from high-altitude Tibetan pastoral areas - Chen, Juanjuan; Luo, Yuanhao; Hao, Yun; Wang, Qian; Wang, Qi (Frontiers in Nutrition, 2025)
IntroductionApproximately 49.3% of individuals living at high altitudes suffer from dyslipidemia. Emerging evidence indicates that gut microbiota can regulate lipid metabolism and cholesterol homeostasis, but the composition and function of gut microbiota in dyslipidemic patients from Tibetan pastoral regions remain unclear.MethodsTo address this, we enrolled a cohort consisting of 22 dyslipidemic patients and 33 healthy controls (HCs) from the Gannan Tibetan pastoral region (average altitude: 3,600 m). Phenotypic data, blood, and fecal samples were collected from all the participants for a metagenome-wide association study based on shotgun metagenomic sequencing.ResultsCompared with HCs, dyslipidemic patients showed a significant reduction in gut microbial diversity. Specifically, the abundance of beneficial species—including Faecalibacterium prausnitzii, Bifidobacterium adolescentis, Bifidobacterium longum, Bifidobacterium bifidum, and Parabacteroides distasonis—was significantly decreased, while opportunistic pathogens such as Veillonella parvula, V. tobetsuensis, Streptococcus oralis, and Streptococcus mitis were notably enriched. Functional prediction revealed that pathways involved in glycolysis, starch degradation, and biosynthesis of L-methionine, L-arginine, L-lysine, L-citrulline, and L-threonine were significantly downregulated in dyslipidemic patients, whereas pathways for the biosynthesis of lipopolysaccharides, fatty acids, polyamines, and (Kdo)₂-lipid A were enriched. Correlation analysis showed that the enriched taxa in dyslipidemic patients were significantly positively associated with total cholesterol (TC), total triglycerides (TG), and low-density lipoprotein cholesterol (LDL-C). In contrast, the enriched functional pathways were significantly negatively correlated with TC but positively correlated with high-density lipoprotein cholesterol (HDL-C).DiscussionThese findings clarify the alterations in gut microbiota composition and function in plateau-dwelling dyslipidemic populations and their associations with blood lipid levels, suggesting potential microbial biomarkers for hyperlipidemia in plateau environments.